Varieties of embodiment in cognitive science. (April 2018) - Alessandroni, Nicolás
This article presents an epistemological multilevel analysis of the embodied cognition studies' programme. It is proposed that within the cognitive-embodied type it is possible to find at least four distinct hypotheses regarding the role of the body in human cognition: (a) body-in-action hypothesis, (b) extended body hypothesis, (c) ecological body hypothesis, and (d) body-as-a-physical-datum hypothesis . The foundations of these hypotheses and some philosophical debates underlying embodiment are discussed in-depth. After briefly addressing the key contributions of social embodied theories, the article presents a hierarchical model that allows for the analysis of the epistemological consequences derived from each embodiment conception. Finally, a prospective epistemological criticism is introduced to provide a comprehensive and contemporary overview of the issue.